Schumpeter and Georgescu-Roegen on the foundations of an evolutionary analysis: The problem of qualitative change, its methodical implications and analytical treatment - Christoph Heinzel (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2006)
Despite the frequent references to Schumpeter's work, his own encompassing methodological approach as worked out by Shionoya (1997) has hardly been considered. In this paper, it is revisited together with Georgescu-Roegen's contributions to economic methodology in view of (i) their contribution to the foundations of an evolutionary analysis in economics and (ii) their mutual complementarity and differences. Both are centred around the issue of qualitative change and its substantial analysis. Schumpeter's analytical distinction between the levels of subject matter and method and his further distinction between stationary and evolutionary economy on the level of subject matter are shown to be decisive for the structure of his analytical system and the determination of an evolutionary analysis on its basis. It is further shown that Georgescu-Roegen's contributions – his evaluation of the entropy law and his consideration of the implications of qualitative change for economic analysis – follow exactly the general structure of Schumpeter's analytical system which they refine or correct. It is argued that they provided together an encompassing general framework for the analysis of economic evolution necessarily different from, but complementary to modern static and dynamic analysis. However, they did neither state nor solve the general theoretical problem of an evolutionary analysis in their sense.
Keywords: B25; O10; B41; B31; 330; evolutionary analysis; Georgescu-Roegen; qualitative change; Schumpeter